International Banking in Cyprus - Yiallouros, Kristie (2009)
The purpose of this dissertation is to analyze the sector of the Cyprus economy that deals with the International Banking or Offshore Banking as otherwise is being called in Cyprus. During the last two decades the island of Cyprus has managed to establish itself as a reputable international financial centre.